Laparoscopic excision of a large extra-adrenal perirenal myelolipoma - Beiko, Darren; Roldan, Hector; SenGupta, Sandip K.; George, Ralph L. (Canadian Urological Association Journal, 2013)
Extra-adrenal myelolipoma is a very rare type of tumour. Laparoscopic removal of extra-adrenal myelolipoma has not been previously reported. We report the first case of laparoscopic excision of a large extra-adrenal perirenal myelolipoma.